Study and development of a GIS for fire-fighting activities based on INSPIRE directive - Lingua, Andrea Maria; Piras, Marco; Musci, maria angela; Noiardo, Francesca; Grasso, Nives; Verda, Vittorio (GEOmedia, 2016)
According to the Annual Fire Report 2013 (European Commission-Joint Research Centre, 2014), there have been 873 forest fires in Europe, in 2013, for a total of 340559 ha of territory. A comparison of this data to that of the previous years, highlights that, when the intended goal is that of preserving the environment and saving human lives, the importance of the correct management of forest fires can not be underestimated. In the past years, the European Union has invested in the development of the INSPIRE Directive (Infrastructure for Spatial Information in Europe) to support environmental policies. Furthermore, the EU is currently working on developing "ad hoc" infrastructures for the safe management of forests and fires. The AF3 EU project (Advanced Forest Fire Fighting), financed by the FP7, addresses the issue of developing innovative tools to handle all stages of forest fires. The project develops a single control center for the coordination of monitoring, manoeuvring, and post-fire operations. The SDI platform (Spatial Data Infrastructure) represents another component which was designed in the context of this project. It is based on a GIS (Geographic Information System) which is able to efficiently integrate multi-modal data. Following an analysis of the state of the art of information systems for forest fire-fighting, and in light of the end-user requirements analyzed within the AF3 project, we propose a geo-topographic database based on the INSPIRE Directive and developed on opensource platforms, which provides interoperability of the data and allows forecasting and monitoring of high-risk areas, decision making, damage estimation, and post-fire management.